The Fragmentary Kinetics of Writing in the Book of Disquiet - Portela, Manuel (2015)
In this article we discuss the notion of literary fragment based on Fernando Pessoa’s Livro do Desassossego [Book of Disquiet], an unfinished work written between 1913 and 1935. Textual witnesses are analyzed as records of the temporal and kinetic dynamics of writing and rewriting, but also as textual units of a work in progress. Self-consciousness of writing emerges both in autograph textual marks, and in the concept of fragment as a piece of text meant for a bibliographic whole. The fragment becomes a textual unit of composition that links the temporality of script acts to the semantic units of a textual whole that remains elusive and only partially determined. Pessoa’s unfinished book project allows us to place this fragmentary logic at the heart of his writing, and see the Book of Disquiet itself as an embodiment of the kinetics of script acts as open explorations of self-consciousness in writing. We address these notions of fragment in the context of our current TEI-XML encoding of both Pessoa’s autograph materials and their editorial versions for the LdoD Archive.